Peru, Flavors & Knowledge. Fundamentals and Methods of Peruvian Cooking - Zubieta Zamudio, Sandra (2017)
Over the past 15 years, Peru has experienced a gastronomic boom. Its cuisine not only currently represents a primary source of Peruvian culture and pride but in very little time, it has made its way into the most privileged circles of international gastronomy. Its restaurants are ranked as the best in Latin America and among the top in the world. Peru has been distinguished by World Travel Awards – for five consecutive years – as the best gastronomy and culinary destination on the planet. Moreover, The World’s 50 Best Restaurants of 2015 gave out awards to three of Peru’s restaurants and nine restaurants were awarded.